Orthopantomography Versus Cone Beam Computed Tomography for the Assessment of the Proximity of Posterior Maxillary Apexes with the Maxillary Sinus: A Cross-sectional Study - Rodriguez, Macarena; Marshall, Maureen; Godoy, Constanza; Richa, Roxana; Niklander, Sven Eric (Current Medical Imaging, 2024)
Background The lack of knowledge of the relation of the maxillary sinus with the apexes of maxillary posterior teeth can lead to important complications during common dental procedures. This can be avoided using different imaging techniques, such as orthopantomography (OPG) and cone beam computed tomography (CBCT). The present study aims to compare the performance of OPG with CBCT in measuring the vertical distance of the apexes of posterior-superior teeth to the maxillary sinus. Methods This study corresponded to a cross-sectional study. OPGs and CBCT scans were obtained from the same individuals, and the qualitative and quantitative vertical distance of the apexes in relation to the maxillary sinus was categorized and measured in mm. Results A total of 28 pairs of OPGs and CBCT scans from the same patients were obtained. About 381 roots were analysed, which included 89 upper first premolars, 51 upper second premolars, 115 upper first molars, and 126 upper second molars. Projection/protrusion was observed with more frequency in molars, specially 1º molars in both OPG (n= 75, 65.2%) and CBCT (n= 31, 27%); however, 106 more cases (27.9%) were classified as projected in the OPG compared to CBCT (p < 0.05). When comparing the performance of the OPG and CBTC for analysing all roots qualitatively, there was a 57.8% agreement between both techniques. This difference was statistically significant (p <0.0001). Statistically significant differences were also observed when comparing the millimetric differences. Conclusion This study showed that OPG is not an accurate technique to observe the relationship between the maxillary sinus and the apexes of the upper posterior teeth. In those cases where precision is required when performing dental procedures in this area, CBCT should be used. When not available, the clinicians should be aware of the limitations of the OPG and add other complementary techniques.
Keywords: Dental